Assessment on reproductive biology of Asian swamp eel, Monopterus javanensis La Cepède 1800 in relation to the impacts of paddy practice management in Kelantan, Malaysia - Sow, Ai Yin; Ismail, Ahmad; Zulkifli, Syaizwan Zahmir; Azmai, Mohammad Noor Amal; Kambali @ Hambali, Kamarul Ariffin (Universiti Putra Malaysia Press, 2020)
In order to understand the life history of the Asian swamp eel, Monopterus javanensis found in paddy fields, the time of maturation of its gonads was studied by using the gonadal somatic index. The peak gonadal somatic index was first found during the ploughing and seedling seasons in 2011 and 2012. This was accompanied by the yellowish egg sac observation made in the eels during the ploughing and seedling seasons, which was indicative of the mid- and early maturation stages of the gonads. However, the decline in GSI from the growing until the harvesting seasons indicated the poor development of gonads since differentiating the sex of the eels was hard. This could be due to the heavy application of pesticides and fertilisers during the growing season as cadmium present as impurities in the fertilisers, which slowly accumulated in the gonads. The findings highlighted the availability of Asian swamp eels for local eel collectors as part of their income and the complexity of heavy metal bioaccumulation in their gonads for safe eel consumption. Overall, the habitat of the Asian swamp eels may induce the differences in the maturation timing for the species.